β-Carboline Silver Compound Binding Studies with Human Serum Albumin: A Comprehensive Multispectroscopic Analysis and Molecular Modeling Study - Ali Alsalme; Rais Ahmad Khan; Arwa M. Alkathiri; Mohd. Sajid Ali; Sartaj Tabassum; Mohammed Jaafar; Hamad A. Al-Lohedan (Bioinorganic Chemistry and Applications)
β-Carbolines (βCs) belong to the naturally occurring alkaloid family, derived from 9H-pyrido[3,4-b]indole, also known as norharmane (Hnor). Knowing the importance of the βCs alkaloid family in biological processes, a comprehensive binding study is reported of four Ag(I) compounds containing the ligand Hnor and having different counteranions, namely, NO3−, ClO4−, BF4−, and PF6−, with human serum albumin (HSA) as a model protein. Different approaches like UV-visible, fluorescence spectroscopy, circular dichroism (CD), and molecular docking studies have been used for this purpose. The fluorescence results establish that the phenomenon of binding of Ag(Hnor) complexes to HSA can be deduced from the static quenching mechanism. The results showed a significant binding propensity of the used Ag(I) compounds towards HSA. The role of the counteranion on the binding of Ag(I) compounds to HSA appeared to be remarkable. Compounds with (ClO4−) and (NO3−) were found to have the most efficient binding towards HSA as compared to BF4−and PF6−. Circular dichroism (CD) studies made clear that conformational changes in the secondary structure of HSA were induced by the presence of Ag(I) compounds. Also, the α-helical structure of HSA was found to get transformed into a β-sheeted structure. Interestingly, (ClO4−) and (NO3−) compounds were found to induce most substantial changes in the secondary structure of HSA. The outcome of this study may contribute to understanding the propensity of proteins involved in neurological diseases (such as Alzheimer’s and Parkinson’s diseases) to undergo a similar transition in the presence of Ag-β-carboline compounds.